2016
DOI: 10.1105/tpc.16.00193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Diversity in Alkaloid Biosynthesis: A Multilane (Diastereomer) Highway for Camptothecin Synthesis in Camptotheca acuminata

Abstract: Camptothecin is a monoterpene indole alkaloid (MIA) used to produce semisynthetic antitumor drugs. We investigated camptothecin synthesis in Camptotheca acuminata by combining transcriptome and expression data with reverse genetics, biochemistry, and metabolite profiling. RNAi silencing of enzymes required for the indole and seco-iridoid (monoterpene) components identified transcriptional crosstalk coordinating their synthesis in roots. Metabolite profiling and labeling studies of wild-type and RNAi lines iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 63 publications
(76 reference statements)
7
119
2
Order By: Relevance
“…As plant metabolites provide indispensable resources for human nutrition, energy and medicine (Butelli et al ., ; Chen et al ., ), dissecting the mechanism of metabolite biosynthesis in plants draws extreme interest (Saito and Matsuda, ; Cardoso et al ., ; Quadrana et al ., ; Zhao et al ., ; Fernie and Tohge, ; Perchat et al ., ; Tian et al ., ). In recent years, the rapid development of analysis approaches for metabolomes and multiomics techniques have greatly improved our knowledge of the naturally occurring metabolic variation in plants and its underlying genetic determinants in several species (Keurentjes et al ., ; Shang et al ., ; Sadre et al ., ; Tohge et al ., ; Wen et al ., ; Fernie and Tohge, ; Rai et al ., ; Westhues et al ., ; Xiao et al ., ; Zhu et al ., ). As one of the most essential crop species, rice ( Oryza sativa L.) not only feeds approximately half of the human population worldwide but also serves as a nutrition source.…”
Section: Discussionmentioning
confidence: 97%
“…As plant metabolites provide indispensable resources for human nutrition, energy and medicine (Butelli et al ., ; Chen et al ., ), dissecting the mechanism of metabolite biosynthesis in plants draws extreme interest (Saito and Matsuda, ; Cardoso et al ., ; Quadrana et al ., ; Zhao et al ., ; Fernie and Tohge, ; Perchat et al ., ; Tian et al ., ). In recent years, the rapid development of analysis approaches for metabolomes and multiomics techniques have greatly improved our knowledge of the naturally occurring metabolic variation in plants and its underlying genetic determinants in several species (Keurentjes et al ., ; Shang et al ., ; Sadre et al ., ; Tohge et al ., ; Wen et al ., ; Fernie and Tohge, ; Rai et al ., ; Westhues et al ., ; Xiao et al ., ; Zhu et al ., ). As one of the most essential crop species, rice ( Oryza sativa L.) not only feeds approximately half of the human population worldwide but also serves as a nutrition source.…”
Section: Discussionmentioning
confidence: 97%
“…Deciphering the genetic control of plant metabolic diversity has attracted a lot of interest, because this topic is essential for enhancing our understanding of the plant metabolome, as well as for human health. Much effort has been made to dissect metabolic pathways, including screening of mutant libraries (Li et al ., ; Yonekura‐Sakakibara et al ., ), analysis of gene families (Yamamura et al ., ; Sadre et al ., ), and comparative genomics studies (Denoeud et al ., ; Huang et al ., ). To obtain deeper insights into genetic and biochemical bases of diversity in the metabolome and to artificially produce natural products with synthetic biology, linkage mapping, and association mapping based on next‐generation sequencing have been applied to metabolomics studies (Luo, ; Alseekh and Fernie, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors were able to capture different metabolic processes and their distribution/biosynthesis across selected plant species, and provided an important metabolic resource for the study of BIA biosynthesis in planta. Metabolite profiling of camptothecin-producing medicinal plants provided an overview of the diverse monoterpenoid indole alkaloids produced (Yamazaki et al, 2003Sadre et al, 2016). Similarly, metabolic profiling of various medicinal plants across different plant families has shown a large diversity of bioactive metabolite classes including flavonoids, saponins and alkaloids.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Using comprehensive metabolite analysis the authors were able to show that camptothecin is derived by the combination of the 2-C-methyl-D-erythritol-4-phosphate (MEP) and shikimate pathways, and not from the mevalonate pathway. A recent study using a metabolite labeling approach across wild-type and RNAi lines of C. accuminata proposed an alternate seco-iridoid pathway for the biosynthesis of monoterpenoid indole alkaloid (Sadre et al, 2016). The authors showed that unlike previously characterized MIAproducing plants such as O. pumila, C. accuminata does not synthesize 3-a-(S)-strictosidine but instead synthesizes strictosidinic acid composed of a mixture of glucoside distereomers as the central MIA intermediate.…”
Section: Metabolomicsmentioning
confidence: 99%